Silica‐associated lung disease: An old‐world exposure in modern industries. Issue 12 (13th September 2019) - Barnes, Hayley; Goh, Nicole S.L.; Leong, Tracy L.; Hoy, Ryan
ABSTRACT: Despite silica dust exposure being one of the earliest recognized causes of lung disease, Australia, USA, Israel, Turkey and other countries around the world have recently experienced significant outbreaks of silicosis. These outbreaks have occurred in modern industries such as denim jean production, domestic benchtop fabrication and jewellery polishing, where silica has been introduced without recognition and control of the hazard. Much of our understanding of silica‐related lung disease is derived from traditional occupations such as mining, whereby workers may develop slowly progressive chronic silicosis. However, workers in modern industries are developing acute and accelerated silicosis over a short period of time, due to high‐intensity silica concentrations, oxidative stress from freshly fractured silica and a rapid pro‐inflammatory and pro‐fibrotic response. Appropriate methods of screening and diagnosis remain unclear in these workers, and a significant proportion may go on to develop respiratory failure and death. There are no current effective treatments for silicosis. For those with near fatal respiratory failure, lung transplantation remains the only option. Strategies to reduce high‐intensity silica dust exposure, enforced screening programmes and the identification of new treatments are urgently required. Abstract : See related Editorial